2005
DOI: 10.1111/j.1462-5822.2005.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Toxoplasma gondii to immunoprivileged organs and role of Toll/interleukin-1 receptor signalling for host resistance assessed by in vivo bioluminescence imaging

Abstract: SummaryToxoplasma gondii infection can lead to lifethreatening systemic disease in the immunocompromised individual and in the developing fetus. Despite intensive investigation in animal models of toxoplasmosis, the processes leading to systemic dissemination remain poorly characterized. In the present study, TLR6-/-and TLR9 -/-animals did not exhibit increased susceptibility to infection. These results suggest that intricate mechanisms regulate TIR-mediated responses during Toxoplasma infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 35 publications
3
134
1
Order By: Relevance
“…Monitoring by BLI of mice infected with H3F33 revealed that during the first days postinfection, R-Luc photon emission was localized mainly in the abdomen. This pattern is similar to that previously observed when mice were infected with tachyzoites expressing firefly luciferase (8,10,20,36). Autopsies carried out shortly after BLI analysis revealed that the signal was localized to the adipose tissue surrounding the ab- dominal organs.…”
Section: Discussionsupporting
confidence: 65%
“…Monitoring by BLI of mice infected with H3F33 revealed that during the first days postinfection, R-Luc photon emission was localized mainly in the abdomen. This pattern is similar to that previously observed when mice were infected with tachyzoites expressing firefly luciferase (8,10,20,36). Autopsies carried out shortly after BLI analysis revealed that the signal was localized to the adipose tissue surrounding the ab- dominal organs.…”
Section: Discussionsupporting
confidence: 65%
“…Tachyzoites were grown in vitro, mechanically lysed from host cells by passage through a 27-gauge needle, and washed twice with PBS supplemented with 1% FCS. Parasite numbers were determined by counting on a hemocytometer, and afterwards, injection of comparable numbers of viable parasites was verified by plaque assay and bioluminescence imaging (11,17). Two groups of six mice were infected with each of the five Toxoplasma strains, WT (A7), PUS1-shi, TBD8 comp , TBD8, and PUS1 KO.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the best-described example of this interaction is in the gut, where Toxoplasma triggers the expression dendritic-cell-and monocyte-recruiting chemokines. While these cells are important for host resistance, the parasite also infects and uses them to disseminate in the host via a Trojan horse-like mechanism (95)(96)(97). In addition, early microarray studies demonstrated that a subset of the host genes modulated by infection were regulated as a result of secreted parasite-and/or host-derived factors being released into the culture medium following infection (45).…”
Section: Toxoplasma Modulation Of Uninfected Cells: Is the Parasite Smentioning
confidence: 99%